Comparison of Image Fusion Techniques: Spatial and Transform Domain based Techniques (International Journal of Engineering and Computer Science, 2015)
Image Fusion is a process of combining image details from  a  number  of  images  into  a  single image,  where  the  resultant  fused  image  will  have most of the details and is more informative  and  complete  than  any  of  the  input  images. Image fusion techniques can increase the quality and populate the application domain of these data. In this paper we present a detailed study and survey on some of the image fusion techniques for  image  fusion  like, primitive  fusion  (Averaging  Method, Select  Maximum,  and  Select  Minimum),  Discrete  Wavelet transform  based  fusion,  Principal  component  analysis (PCA)  based  fusion  etc.  Study and Comparison of all the techniques helps to determine the better approach for its future research and implementation.